Determinants of managers' voluntary turnover in the Algerian companies: case study - Benghebrid, Riad (Management and Entrepreneurship: Trends of Development, 2024)
The changes in the economic environment in Algeria, especially after the openness of the national market to global trade since the beginning of the nineties and the competitive advantages it brought, led to shifts at the level of value creation, which moved from exploiting natural resources to valuing the human resources, and here many companies have found themselves faced with the necessity of employing human resources capable of management and bearing responsibility for improving the product or service while retaining it to enhance its survival, that is, preserving it and reducing voluntary turnover rates. Within this context, the current research paper seeks to identify the most important determinants that affect voluntary turnover rates in the Algerian companies. To achieve this endeavour, a quantitative approach was employed, we distributed a questionnaire to 87 managers active in the Algerian Canning Plant, holding various positions within the company under study and they possess previous experience in other companies. Through SPSS program, Principal Components Analysis (PCA) was employed in analyzing the statistical data collected. The results revealed that managers’ voluntary turnover in Algerian company is linked to five variables, which are listed in descending order as follows: the job content and management style, career path planning, working conditions, formation level and work alternatives, and material incentive.JEL Classification: J24, O15